(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
In the current study we investigated the Rana ridibunda tadpole’s liver arginase limited trypsinolysis in order to obtain information about the sensitive bonds towards proteases, as well as about the structural and functional interrelations during metamorphose. After 18 h of limited trypsinolysis in the early stages of tadpole development (21–27) appeared relatively massive fragments, the degradation of fragments deepen concomitant to the real metamorphose approach (28–29 stages). Enzyme pre-incubation with Mn2+ leads to stabilization of activity and protects the enzyme from proteolytic inactivation.